Why some teachers easily learn to use a new virtual learning environment: a technology acceptance perspective. Issue 3 (2nd April 2016) - Rienties, Bart; Giesbers, Bas; Lygo-Baker, Simon; Ma, Hoi Wah Serena; Rees, Roger
Abstract : After a decade of virtual learning environments (VLEs) in higher education, many teachers still use only a minimum of its affordances. This study looked at how academic staff interacted with a new and unknown VLE in order to understand how technology acceptance and support materials influence (perceived and actual) task performance. In an experimental design, 36 participants were split into a control (online help) and experimental (instructor video) condition and completed five common teaching tasks in a new VLE. In contrast to most technology acceptance model research, this study found that perceived usefulness of the VLE was not related to (perceived) task performance. Perceived ease of use was related to intentions and actual behaviour in the VLE. Furthermore, no significant difference was found between the two conditions, although the experimental condition led to a (marginal) increase in time to complete the tasks.